The Influence of Customer Perception, Brand Fit, and Brand Credibility on Brand Image: A Case Study of Naming Rights of BT Batik Trusmi - Jihan Rhaudhatul Jannah; Ramlah Puji Astuti; Tiara Muthiarsih (Mabsya: Jurnal Manajemen Bisnis Syariah, 2026)
This study examines the influence of customer perception, brand fit, and brand credibility on BT Batik Trusmi's brand image in the case of the cancellation of the "BT Batik Trusmi Cirebon Station" naming rights program. A quantitative method with an associative design was employed, involving 200 respondents who were aware of the program's cancellation. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression. The results showed that all three variables had a positive and significant effect on brand image, both partially and simultaneously. Customer perception was the most dominant variable, followed by brand fit and brand credibility. The adjusted R-squared value of 0.592 indicates that 59.2% of the variance in brand image can be explained by these three variables. These findings suggest that public perception, collaboration suitability, and brand credibility are important to maintain, especially when changes or cancellations of marketing programs occur in the public space.